Dielectric dispersion and ac conduction phenomena of Li2O−Sb2O3−PbO−GeO2:Cr2O3 glass system. (July 2015) - Vijay, R.; Ramesh Babu, P.; Ravi Kumar, V.; Piasecki, M.; Krishna Rao, D.; Veeraiah, N.
Abstract: Lithium antimony lead germanate glasses doped with different concentrations of Cr2 O3 (ranging from 0 to 0.5 mol %) were synthesized. The optical absorption and ESR spectral studies have indicated that there is a gradual increase in presence of octahedral chromium ions with increase of Cr2 O3 concentration in the glass network. These studies have also revealed that a fraction of chromium ions get oxidized into Cr 5+ and Cr 6+ states. IR and Raman spectroscopic studies have pointed out that there is an increasing degree of depolymerization of the titled glass network with increase of Cr2 O3 content. The dielectric parameters (viz., dielectric constant, loss and electrical modulus coefficients measured over a wide range of frequency and temperature) and also ac conductivity were found to increase with increase of Cr2 O3 content. The reasons for such increase were discussed quantitatively in terms of various polarization mechanisms coupled with structural variations of the glass network.